Anthropological profile of goalball athletes - brief systematic review - Utvic, N.; Dejanovic, M.; Nikolic, M.; Prakash Dubey, V. (Homosporticus, 2019)
Introduction: Goalball is a sport designed for persons with an impaired sense of sight. It is one of the most popular sports with the ball in the blind and sight-impaired persons. The body composition with goalball players is crucial for studying due to insufficient physical activity, which aims to characterize persons with sight invalidity issue. Methods: The articles from the following electronic databases have been studied: PubMed/Medline, Cihnal, Embase, Open- J-Gate, Science Direct and Google Scholar. The articles published between 2004 and 2019 have been studied, with a focus on the anthropological profile of goalball players. The inclusion criteria were divided into four sections: study strategy, study design, type of measurement outcome, exclusion criteria. The procedures were carried out in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) statement. Results: Out of 108 articles collected, 14 articles have been analyzed in detail on the grounds of databases and consequently a conclusion has been provided. Conclusion: The body height is crucial for contributing to a greater arm span, which means greater space coverage, as well as a percentage of muscle tissue connected to muscle strength